Effects of liquid metabolites from Lactobacillus plantarum on gastrointestinal health, cholesterol level and growth performance of broiler chickens - Cheng, Xiang Feng (2011)
The use of antibiotics as growth promotants has become unacceptable. Liquid metabolites seem to have a bright future as antibiotic substitutes because of their natural antibacterial properties. Three experiments were conducted to study the effect of feeding liquid metabolite (LM) mixtures produced from 4 strains of Lactobacillus plantarum on growth performance in broiler chickens. Different liquid metabolites produced by RG14, RG11, RS5, and RI11 of locally isolated L. plantarum were studied against the indicator strain P. acidilactici in the first experiment. The pH, bacteriocin activity, inhibitory zone diameter and viable plate count of liquid metabolites from four L. plantarum strains RG11, RG14, RI11 and RS5 and their mixtures were determined. The studies showed that metabolites produced by the strains of L. plantarum have different abilities to inhibit the indicator; especially metabolite mixtures exhibited stronger bacteriocin activity and clear zone diameter compared to single RS5, RI11, RG14 and RG11 strains. Mixtures of these metabolites further enhance the inhibitory effects against the indicator P. acidilactici. These metabolites have synergistic effects as they could be applied as biopreservatives in food industry and feed additives for animal. In the second experiment, liquid metabolite mixtures produced by four strains of L. plantarum were used in feed as antibiotics replacement in broiler chickens. A total of 294 male Cobb broiler chickens were divided into 7 treatments with different diets: 5 levels of liquid metabolites (LM) (0.5%, 1.0%, 1.5%, 2.0%, and 2.5%) and 2 controls (negative control and positive control). Improved growth performance, reduced Enterobacteriaceae and increased lactic acid bacteria counts and increased small intestine villi height were found in the treatments supplemented different levels of metabolite mixtures. The chicken supplemented with 1.0% LM had the best results among the treatment groups, but not significantly different (P < 0.05) with 0.5% LM treatment. The third experiment was conducted using drinking water to study growth performance, apparent digestibility, meat and blood plasma total cholesterol in 6 weeks broiler chicken. Compared with metabolites in feed, administering metabolites in drinking water is easy to handle and not sensitive to environment temperature especially in the farm conditions. A total of 432 male Cobb broiler chickens were divided into 6 groups based on metabolites level in drinking water: four levels of liquid metabolites mixtures (0.25%, 0.50%, 0.75% and 1.00%) and 2 controls (negative control and positive control). Improved growth performance, increased feed apparent digestibility and lowered meat and blood plasma total cholesterol concentrations were found in the treatments supplemented different levels of metabolite mixture. Furthermore, similar or better effect in enhancing chicken growth performance of metabolites compared to antibiotic growth promotant was observed in this study. The chickens supplemented with LM in drinking water had no significantly different with each other. The chickens supplemented with 0.25% LM had the best results among the treatment groups. LM combinations of 4 strains RS5, RI11, RG11, and RG14 at level of 0.25% can be used in drinking water as replacement of antibiotic in poultry production. In conclusion, mixture of four strains RG11, RG14, RI11 and RS5 from Lactobacillus plantarum has synergistic effects against the indicator strain P. acidilactici; feeding this metabolite mixture in diets or drinking water has beneficial effects on growth performance, faecal microflora, small intestine villi height, apparent digestibility, meat and blood plasma cholesterol in broiler chickens. It implies liquid metabolites produced by RG14, RG11, RS5, and RI11 of locally isolated L. plantarum are potential alternatives to antibiotics that could be used as growth promoter in broiler chickens.